Enhancing Potential: Performance Evaluation of Arabic Language Teachers - Misra, Misra; Sahraini, Sahraini; Kartini, Kartini (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
This study aims to contribute theoretically to the development of educational science and provide practical insights for Madrasah Tsanawiyah Negeri Towuti and similar institutions in evaluating teacher performance to enhance educational quality. The research employs an evaluative approach using the discrepancy model, conducted through qualitative methods, including observation, interviews, and document analysis, focusing on the performance evaluation of Arabic language teachers at MTsN Towuti. The findings reveal that Arabic teachers excel in lesson planning, as evidenced by the comprehensive administrative preparations at the start of the academic year. However, while overall performance was good during the implementation phase, challenges such as ineffective classroom management, monotonous teaching methods, and insufficient encouragement for creative thinking were noted. In the assessment phase, teachers demonstrated strong performance in designing assessment tools, applying diverse strategies to monitor student progress, and providing constructive feedback, aligning with school and national standards. The evaluation concludes that the teachers' performance in planning, implementation, and assessment is generally good, adhering to established standards. The study recommends that these strengths be maintained and further enhanced. The implications suggest that stakeholders should pay greater attention to teacher qualifications, advocating for more extensive training and certification programs. Practically, the findings serve as constructive feedback for Arabic language teachers to improve their performance further.